2008
DOI: 10.1007/s12230-008-9008-4
|View full text |Cite
|
Sign up to set email alerts
|

Internal Heat Necrosis of Potato—A Review

Abstract: Non-pathogenic necroses of potato tubers have been described in the literature since the early 20th century using different names including internal rust spot, internal browning, physiological internal necrosis, internal brown fleck, chocolate spot, internal brown spot and internal heat necrosis. These reports very likely describe either the same, or a collection of similar disorders, falling under the general umbrella of "internal necrosis", with the expression of symptoms being significantly altered via geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 37 publications
2
25
0
2
Order By: Relevance
“…For TER, we identified four QTL on chromosomes I, III, V, and VI. Tuber end rot could be a physiological disorder of potato tubers with similar symptoms as the "internal necrosis" syndrome well described by Yencho et al (2008). In our case, a progressive rot from the stem end of the tuber affecting all periderm, vascular ring, and parenchymal tissue appears after harvest.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…For TER, we identified four QTL on chromosomes I, III, V, and VI. Tuber end rot could be a physiological disorder of potato tubers with similar symptoms as the "internal necrosis" syndrome well described by Yencho et al (2008). In our case, a progressive rot from the stem end of the tuber affecting all periderm, vascular ring, and parenchymal tissue appears after harvest.…”
Section: Discussionsupporting
confidence: 67%
“…Those genes were located on chromosomes I, II, and VIII. Different studies have also shown that low calcium (Ca) levels could be correlated with increased tuber IHN (Yencho et al, 2008). In our study, QTL in chromosomes I, III, and VI were detected for TER.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…This is justified from a chip processing perspective because tubers are not stored and processed year round at southern locationsthey are processed within a few days of harvest; as a result, resistance to cold-induced sweetening (Sowokinos, 2001) is not a critical trait. Conversely, resistance to internal heat necrosis (Yencho et al, 2008) is important at southern but not northern locations. Figure 4 provides some empirical support for the traditional mega-environments of North vs. South, but there is more variation between southern locations than there is between the mega-environments.…”
Section: Discussionmentioning
confidence: 99%